Cyclical change - Gelderen, Elly van (Linguistik aktuell, 2009)
Linguistic Cycles are ever present in language change and involve a phrase or word that gradually disappears and is replaced by a new linguistic item. The most well-known cycles involve negatives, where an initial single negative, such as not, is reinforced by another negative, such as no thing, and subjects, where full pronouns are reanalyzed as endings on the verb. This book presents new data and insights on the well-known cyclical changes as well as on less well-known ones, such as the preposition, auxiliary, copula, modal, and complementation cycles. Part I covers the negative cycle with c.